Critiquing Islamic Feminism from a Social Psychological Perspective - Constance, Alberta (PT. Riset Press International, 2023)
Islamic feminism represents a feminist discourse that seeks to reinterpret the Qur'an from a contemporary egalitarian perspective, challenging the traditional and patriarchal interpretations of Islam. By doing so, Islamic feminists aim to reclaim an ethical vision of the Qur'an, especially concerning verses that have historically deprived women of equal rights within the family and society. Through their efforts, Islamic feminism introduces new discourses and debates on gender relations within an Islamic context, fostering a greater gender and religious consciousness and furthering the cause of gender equality. This paper takes a critical approach to Islamic feminism, employing a social psychological perspective on gender, using Abdulkarim Soroush's theory. According to Soroush, revelation is understood as the prophet's inspired expression resulting from his religious experience. It is not a direct word from God but rather Muhammad's interpretation of a divine experience. In this context, the paper examines the lived experience of the prophet as a man in a specific historical epoch where women's lived experiences were not adequately represented. It highlights how the revelation or the Qur'an is rooted in a male lived experience. The paper begins with an overview of Islamic feminists and Islamic reformists, both of whom strive to view the revelation as the prophet's word rather than attributing the non-scientific content of the Qur'an directly to God's word. Subsequently, it delves into a critique of Islamic feminism through the lens of Abdulkarim Soroush's theory on recognizing the revelation as the prophet's word. Additionally, the paper draws upon gender theories from the field of social psychology to provide a comprehensive analysis of the subject matter.